KAJIAN KERAGAMAN GENETIK BURUNG KAKATUA TANIMBAR (Cacatua goffini, Finsch) MENGGUNAKAN PENCIRI "RAPD" - Dwi Astuti; Siti N. Priyono; Heddy Julistiono; Dedy Duryadi (BERITA BIOLOGI, 1998)
The study was conducted to analyse genetic diversity of Goffini Finsch Cockatoo (Cacatua goffini Finsch) bird using RAPD (Random Amplified Polymorphic DNA) marker.PCR (Polymerase Chain Reaction) was performed on DNA samples extracted from 14 birds,using 18 random 10-merprimers and 2 random 12-merprimers. Fourteen out of 20 primers (70 %) successfully amplified DNAfragmens and 11 out of 14 primers (78,57 %) generated 1-2 specific alkies.The result clearly demonstrated that the RAPD marker allows for genetic diversity analyses of these birds in efficiently. Tree of relationship among 14 birds showed that there were two groups in the population ofGoffin 's Cockatoo.